Training Needs Related to the Utilization of Special Technological Innovations in the Education and Rehabilitation of People with Hearing Disabilities {Survey Study of Teachers in the Special Education Institute for the Rehabilitation of the Deaf and Dumb in Damascus City} - Ebrahem, Juma; Ghalia , Masri (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to identify the training needs of the teachers of special education in order to utilize the special technological innovations in the rehabilitation and education of people with hearing disabilities in Damascus city; it also aims to identify the teachers' views, the difficulties that hinder their utilization of the technological innovations, and their proposals to activate their utilization. To achieve the objectives of the research, the researcher designed a questionnaire consisted of (43) items, divided into five fields. After confirming their sincerity and persistence, the research tool was applied on the research sample consisting of (62) teachers and Sign Language teachers; they make up the original community of the study. After conducting the statistical treatments necessary, the research showed the following results: - The degree of the training needs related to the utilization of technological innovations in the rehabilitation and education of people with hearing disabilities was generally high; the total degree is (2.42). - The lack of statistically significant differences in the average of training needs related to the utilization of technological innovations by teachers due to job title and academic qualification variables. - The presence of positive attitudes towards implementing technological innovations by the members of the teaching and educational staff. - The most important obstacles to the utilization of technological innovations in education from the point of view of the sample were as follows: the lack of training courses on utilizing the technological innovations during the service, and the lack of adequate preparations of classrooms for technical use. - The most important proposals presented by the sample to activate the utilization of innovations were as follows: the preparation of a guide for teachers in different disciplines to utilize the technological innovations.